PENGOLAHAN LIMBAH PERTANIAN MENJADI BRIKET, BOKASHI, SILASE, DAN KOMPOS CASCING DI DESA SIDOREJO GODEAN - Mulasari, Surahma Asti; Tentama, Fatwa; Sulistyawati, Sulistyawati; Sukesi, Tri Wahyuni (BAGIMU NEGERI : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2018)
Bantut, Kemirisewu and Dongkelan have abundant of agricultural crop yield, on another side, the negative impact is raising due to untreated of crop yield. KKN PPM program was aimed to help the lokal community in solve that environmental problem by empowering the community through KKN PPM student. By this activity was hoped that KKN PPM student, institution and community group will change their attitude in treating the agricultural waste. Counseling, training and mentoring were used as a method of this program. Students and lecturer shared knowledge about the utilization of the waste such as briquette, bokashi, silage, and “cascing” fertilizer. In this activity, also be followed by post-production activities in using biomass briquettes (biobriket) as an alternative fuel in the household basis, bokashi products and “cascing” that rules as fertilizer for increased farming production. Silage was a function as increase livestock production. The outcome of this KKN PPM program was the improvement of environmental management system, better management of agricultural waste, improvement of community education and participation and increases of community self-support. At the end of program, Bokashi, briquettes, silage, and cascing fertilizer were produced.